Prototype of temperature and time rushing control system of soybeans boiling process for tofu manufacture based on AT89S52 microcontroller using IC LM35 - Afdi Marta (Department of Physics – Universitas Negeri Padang UNP, 2014)
The objective of these research are to determine the transfering function and sensitivity of the sensor IC LM35, to describe the physical shape and dimensions of the system controlling the temperature and time in the process of boiling porridge of soy, and to determine the static of characteristics of temperature control system based on microcontroller AT89S8252 with LM 35 sensors for boiling the soy porridge process. This research can be classified into engineering research. Data collection techniques are both direct and indirect measurement. Direct measurement ise used to measurement the temperature of soy porridge process. On other hand, indirect measurement is used to determine the accuracy and precision of the system in the manufacture of soy porridge boiling out. Based on the analysis of the data can be presented three results of research. First, the voltage output temperature sensor IC LM 35 is directly proportional to temperature. Second, description and temperature control system that describe each part of the system. Finally, instrument temperature control has a very high accuracy and precision of 96.96% on average.Keywords: Prototipe, Controlling System, Temperature, Time, Soy boiling , IC LM35